Use of fibre palm as a local alternative litter material for broiler production: Effect on broilers’ welfare and performance - M, BEN LARBI; SAIDANI, M; SOUF, I BEN; HAMDI, N M (The Indian Journal of Animal Sciences, 2024)
This study evaluated the quality of three types of bedding materials and investigated their effects on growth performance and the welfare state of broilers. The experiment was carried out on 48,540 broilers equitably distributed in three poultry houses with three distinct types of litter material: chopped wheat straw, wood shavings, and palm fibre. The quality of the litter was assessed by scoring each type of litter, determining their absorbency, humidity and counting darkling beetle population. Growth performance was measured and welfare parameters were evaluated. Litter evaluation results revealed that wheat straw retained less water (76%), was the most humid at the end of the trial (69.82%), and was in very bad condition since the third week of the experiment, while palm fibre has the highest water-holding capacity (175.6%). Compared to wood shavings, palm fibre had the same litter quality assessment until the fourth week of the trial, and moisture rates were comparable. Regarding growth performance, there were no significant differences among litter types. However, significant effects on the health state of broilers were noted. The highest incidence of footpad lesions, pododermatitis and hock burns were recorded in broilers raised on wheat straw litter, while wood shavings and fibre palm showed comparable results. Therefore, palm fibre could be a local alternative litter material and can replace wood-shaving litter in broiler farms.